Pengaruh Rasio Keuangan Pemerintah Daerah Terhadap Indeks Pembangunan Manusia - Zul Hendri; Meileni Yafiza (LPPM ISNJ Bengkalis, 2020)
This research was conducted to find out how much influence the local government financial ratios have on the human development index, the ratio used is the ratio of the degree of decentralization, the ratio of regional financial dependence, the ratio of regional financial independence, the ratio of the effectiveness of local own revenue and the ratio of the effectiveness of the local tax. The type of data from this research is quantitative descriptive using primary and secondary data. The data analysis technique used is multiple linear regressions. The results of this research are that there is a very strong relationship between the degree of decentralization, the ratio of regional financial dependency, the ratio of regional financial independence, the ratio of the effectiveness of local own-source revenue and the ratio of the effectiveness of local taxes and simultaneously affect the human development index.